Birefringence measurement of polymer photonic crystal fibers infiltrated with liquid crystals by depolarization of light effect - Budaszewski, Daniel; Domański, Andrzej W (Photonics Letters of Poland, 2014)
In the paper we estimate group birefringence of polymer photonic crystal fiber partially infiltrated with nematic liquid crystal 5CB. To calculate group birefringence we use a novel method proposed by our group based on depolarization phenomena of partially coherent light that takes place in anisotropic media such as liquid crystals and birefringent optical fibers. Taking into consideration spectral parameters of the light source and degree of polarization at the output of the fiber we calculated effective birefringence of the fiber partially infiltrated with liquid crystal. The results for empty polymer optical fiber were compared with the data provided by the manufacturer to confirm feasibility of applied method. Full Text: PDF References T.R. Woliński, S. Ertman, D. Budaszewski, M. Chychłowski, A. Czapla, R. Dąbrowski, A.W. Domański, P. Mergo, E. Nowinowski-Kruszelnicki, K.A. Rutkowska, M. Sierakowski, M. Tefelska, "Emerging photonic devices based on photonic liquid crystal fibers", Phot. Lett. Poland 3, 20 (2011). CrossRef S. Ertman, A.H. Rodríguez, M.M. Tefelska, M.S. Chychłowski, D. Pysz, R. Buczyński, E. Nowinowski-Kruszelnicki, R. Dąbrowski, T.R.Woliński, "Index Guiding Photonic Liquid Crystal Fibers for Practical Applications", IEEE J. Lightwave Technol.30, 1208 (2011). CrossRef M.M. Tefelska, M.S. Chychłowski, T.R. Woliński, R. Dąbrowski, W. Rejmer, J. Wójcik, "Propagation Effects in Photonic Liquid Crystal Fibers with a Complex Structure", Acta Phys. Pol. A 118, 1259 (2010). DirectLink A. Siarkowska, M. Jóźwik, S. Ertman, T.R. Woliński, V.G.Chigrinov, "Photo-alignment of liquid crystals in micro capillaries with point-by-point irradiation", Opto-Electron Rev., 22, 3, 178, (2014). CrossRef A. Argyros, "Microstructured Polymer Optical Fibers", J. Lightwave Technol. 27, 1571 (2009). CrossRef M.A. Eijkelenborg, M.C.J. Large, A. Argyros, J. Zagari, S. Manos, N.A. Issa, I. Bassett, S. Fleming, R.C. McPhedran, C.M. de Sterke, N.A.P. Nicorovici, "Microstructured polymer optical fibre", Opt. Expr. 9, 319 (2001). CrossRef A. Stefani, K. Nielsen, H.K. Rasmussen, O. Bang, "Cleaving of TOPAS and PMMA microstructured polymer optical fibers: Core-shift and statistical quality optimization", Opt. Commun. 285, 1825 (2012). CrossRef C. Markos, A. Stefani, K. Nielsen, H. K. Rasmussen, W. Yuan, O. Bang, "High-Tg TOPAS microstructured polymer optical fiber for fiber Bragg grating strain sensing at 110 degrees", Opt. Expr. 21, 4758 (2013). CrossRef J. Anthony, R. Leonhardt, A. Argyros and M. C. J. Large, "Characterization of a microstructured Zeonex terahertz fiber", J. Opt. Soc. America B, Vol. 28, 5, 1013, (2011). CrossRef G. Emiliyanov, J. B. Jensen, O. Bang, P. E. Hoiby, L. H. Pedersen, E. M. Kjaer, L. Lindvold, "Localized biosensing with Topas microstructured polymer optical fiber", Opt. Lett. 32, 460 (2007). CrossRef D. Budaszewski, A. K. Srivastava, A. M.W. Tam, T. R. Woliński, V. G. Chigrinov, H-S. Kwok, "Photo-aligned ferroelectric liquid crystals in microchannels", Opt. Lett. 39, 16 (2014). CrossRef W.K.Burns, "Degree of polarization in the Lyot depolarizer", J.Lightwave Technol. LT-1, 3, 475(1983). CrossRef A.W. Domański, "Polarization degree fading during propagation of partially coherent light through retarders", Opto−Electron. Rev. 13, 171–176 (2005). DirectLink J.I. Sakai, S. Machida, and T. Kimura, "Degree of polarization in anisotropic single−mode optical fibers", IEEE J.Quantum Elect. OE−18, 488–495 (1982). CrossRef A.W. Domański, M.A. Karpierz, A. Kujawski, and T.R.Woliński, "Polarimetric Fiber Sensors for Partially Polarized Laser Source", Proc. 12th Intern. Congress Laser 95, Springer−Verlag, Berlin, 684–687 (1996). CrossRef A.W. Domański, D. Budaszewski, M. Sierakowski, and T.R. Woliński, "Depolarization of partially coherent light in liquid crystals", Opto−Electron. Rev. 14, 61–66 (2006). CrossRef D. Budaszewski, A. W. Domański, T. R. Woliński, "Novel bandwidth measurement method for partially coherent light sources", IEEE Instrumentation and measurement technology conference proceedings IMTC 2007 (2007). CrossRef N. Shibata, A. Nakazono, Y. Inoue, "Interference between two orthogonally polarized modes traversing a highly birefringent air-silica microstructure fiber", J. LightwaveTechnol., 23, 3 (2005). CrossRef F. Tang, X. Wang, Y. Zhang, W. Jing, "Characterization of birefringence dispersion in polarization-maintaining fibers by use of white-light interferometry", Appl.Opt, 46, 19 (2007). CrossRef P. Hlubina, T. Martynkien, W. Urbanczyk, "Measurements of intermodal dispersion in few-mode optical fibres using a spectral-domain white-light interferometric method", Meas. Sci. Technol. 14, 784 (2003). CrossRef R. Chlebus, P. Hlubina, D. Ciprian, "Spectral-domain tandem interferometry to measure the group dispersion of optical samples", Optics and Lasers in Engineering, 47, 173 (2009). CrossRef P. Hlubina, M. Szpulak, L. Knyblova, G. Statkiewicz, T. Martynkien, D. Ciprian, W. Urbanczyk, "Measurement and modelling of dispersion characteristics of a two-mode birefringent holey fibre", Meas. Sci. Technol. 17, 626 (2007). CrossRef